Synthesis and selective reactivity of 14β-formyl 19-norsteroids - Hoadley, Clarissa (Department of Chemistry, 2016)
A synthetic route to 3-methoxy-16-methyl-14,17α-ethanoestra-1,3,5(10)-triene-15,16,l 7β3-triol 17β3-acetate was devised, based upon cycloaddition of a dienophilic 'propyne equivalent' to 3-methoxyestra-1,3,5(10),14,16-pentaen-17-yl acetate. The dienophile chosen for this purpose, methyl propiolate, reacted with the diene regio- and stereoselectively to give methyl 17β3-acetoxy-3-methoxy-14, 17α-ethenoestra-1,3,5(10), 15-tetraene-16- carboxylate. The resulting cycloadduct was chemoselectively hydrogenated to give methyl 17β3-acetoxy-3-methoxy-14,17α-ethanoestra-1,3,5(10),15-tetraene-16-carboxylate. Attempted 1,2-reduction of this compound was unsuccessful and an indirect synthetic sequence to key intermediates for oxidative cleavage to 14(3-formyl 19-norsteroids was undertaken. cis-Dihydroxylation of the dihydrocycloadduct gave an isomeric mixture of the 15a,16a- and 15β3,16β3-diols, which were protected via acetonide formation. Sequential reduction of the ester functionality, chemoselective mesylation of the 161-hydroxy group of the resultant 161-hydroxymethyl 17-alcohols, and reduction of the 161-mesylate, gave the isomeric 16-methyl 15,16-acetonides. 17-Acetylation followed by diol deprotection gave the desired 3-methoxy-16-methyl-14,17a-ethanoestra-1,3,5(10)-triene-15,16,17(3-triol 17(3- acetates. A more direct and efficient route entailed conjugate addition of thiophenol to the dihydrocycloadduct to give methyl 17β3-acetoxy-3-methoxy-15a-phenylthio-14, 17α-ethanoestra- l,3,5(10)-triene-16f3-carboxylate. Reductive deoxygenation of the functionality on C(16) gave the 16β3-methyl 15a-phenylthio intermediate, the corresponding sulfoxide of which underwent smooth thermal elimination to yield the key intermediate, 3-methoxy-16- methyl-14,17α-ethanoestra-l,3,5(10),15-tetraen-17f3-ol. This hydroxy olefin, and the corresponding 17-acetate, underwent cis-dihydroxylation to give the desired 16-methyl 15,16-diols in superior overall yields. These intermediates underwent oxidative cleavage to give 17α-acetoxy-3-methoxy-20-oxo-19-nor-14β3-pregna-l,3,5(10)-triene-14-carbaldehyde. This strategy and related adaptations led to the synthesis of a variety of 17-substituted 14(3- formyl 19-norsteroids, including the 14β3-formyl analogue of estrone. Chemoselective reaction of this compound led to the synthesis of 14f3-hydroxymethyl- and 14β3-vinyl analogues of estradiol. Intramolecular aldol condensation of 17a-acetoxy-3-methoxy-20- oxo-19-nor-14β3-pregna-1,3,5(1 O)-triene-14-carbaldehyde gave 17 a-hydroxy-3-methoxy- 14,l 7β3-prop-172-eno-14β3-estra-1,3,5(10)-triene-171-one, which was converted into a novel bridged honnone analogue, (171S)-14β3,17β3-prop-172-eno-14β3-estra-1,3,5(1 O)-triene- 3, l 7a,171-triol. Further, it was shown that the 14β3,l 7β3-prop-172-eno 17a,l 71-diol underwent 16(16-+ l71)abeo rearrangement to 3-methoxy-14,17a-ethano-17a-homoestral, 3,5(10),15-tetraen-17a-one, which, on reduction, gave the corresponding 17ahomoestradiol analogues. Hormone analogues that were synthesised during this investigation were subjected to biological evaluation, and the results and structure activity implications reported.